A Historical Guide to the Future of Marriage for Same-Sex Couples - Goldberg, Suzanne B. (Columbia Journal of Gender and Law, 2006)
History and tradition have emerged, together, as contemporary flagship arguments for limiting marriage to different-sex couples. According to advocates of “traditional marriage,” same-sex couples can be excluded from marriage today because marriage always has been reserved to male-female couples. Further, some contend, the restriction of marriage to different-sex couples has long been understood as necessary to provide channels to control naturally procreative (i.e., male-female) relationships. However popular these claims might be in op-ed pieces and on talk radio, when they are made in the litigation context, the question is not whether they have rhetorical appeal but rather whether they can explain the State’s different marriage rules for gay and non-gay couples. For this purpose, broad-brush invocations of marriage’s history will not suffice.